PENGARUH BRAND IMAGE, INFLUENCER MARKETING, DAN WORD OF MOUTH TERHADAP MINAT BELI PRODUK LE MINERALE PADA MAHASISWA UNIVERSITAS 17 AGUSTUS 1945 SURABAYA - Bagus Pranjaya; Ida Ayu Nuh Kartini (Cahaya Ilmu Bangsa, 2025)
This study aims to analyze the influence of brand image, influencer marketing, and word of mouth on the purchase interest of Le Minerale products among students of the University of 17 August 1945 Surabaya. This study uses primary data, namely data that is directly collected or obtained by researchers from the research object, where this study uses a questionnaire data collection technique. This study uses a quantitative method with a population of all students of the University of 17 August 1945 Surabaya as many as 75 people. The data analysis technique in this study is multiple linear regression analysis, the coefficient of determination (r2) and the hypothesis test uses the t test and f test. The results of this study are that Brand Image (X1) has a significant effect on Purchase Interest (Y) with a t count of 2.398 and a sig. value of 0.019 <0.05. Influencer Marketing (X2) has a significant effect on Purchase Interest (Y) with a t count of 3.151 and a sig. value of 0.002 <0.05. Word of Mouth has a significant effect on Purchase Interest (Y) with a t count of 2.812 and a sig. value of 0.006 <0.05. The conclusion of the results of this study is that the variables of brand image, influencer marketing and word of mouth have a significant effect on students of the University of 17 August 1945 Surabaya. Where this means that the better the brand image, influencer marketing and word of mouth, the more it can increase consumer purchase interest.